Positive pole piece, electrochemical device and electronic device
By setting a first coating to regulate the particle size and specific surface area of the lithium-ion battery in the positive electrode sheet of the lithium-ion battery, the problem of the lithium-ion battery being prone to internal short circuit during the nailing process is solved, and its safety performance and cycling performance are improved.
Patent Information
- Application Number
- CN202510034212.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-15
AI Technical Summary
Existing lithium-ion batteries are prone to internal short circuits during the nailing process, affecting their safety performance and cycling performance.
A first coating is provided in the positive electrode sheet, including a lithium-containing material and a conductive material, and the Dv99 of the lithium-containing material and the specific surface area are controlled in the range of 500 nm to 1000 nm and 5m2/g to 50 m2/g to reduce short-circuit points and increase short-circuit resistance.
By reducing short-circuit points and increasing short-circuit resistance, the heat generation power during short-circuit is reduced, the contact between the positive electrode current collector and the first coating and the positive electrode material layer is improved, electron transmission is promoted, and the safety and cycling performance of the electrochemical device are improved.
Smart Images

Figure CN119833559A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical technology, and in particular to a positive electrode sheet, an electrochemical device and an electronic device. Background Art
[0002] Electrochemical devices (such as lithium-ion batteries) have entered our daily lives with the advancement of technology and the improvement of environmental protection requirements. With the widespread popularity of lithium-ion batteries, their cycle performance has been increasingly valued by users, and consumers, after-sales service providers and manufacturers have also put forward new requirements for the safety performance of lithium-ion batteries.
[0003] However, the current technology to improve the safety performance of lithium-ion batteries is not mature. During use, the positive and negative pole pieces of lithium-ion batteries often come into contact with each other during the nailing process, or the positive and negative pole pieces are connected by nails, which leads to internal short circuits, affecting the safety performance of lithium-ion batteries and reducing the cycle performance. Therefore, the market is in urgent need of a lithium-ion battery with good safety and cycle performance. Summary of the invention
[0004] The purpose of the present application is to provide a positive electrode plate, an electrochemical device and an electronic device to improve the safety performance and cycle performance of the electrochemical device.
[0005] It should be noted that in the invention content of this application, lithium-ion batteries are used as an example of electrochemical devices to explain this application, but the electrochemical devices of this application are not limited to lithium-ion batteries. The specific technical solutions are as follows:
[0006] The first aspect of the present application provides a positive electrode plate, the positive electrode plate comprising a positive electrode current collector, a first coating and a positive electrode material layer, the first coating is arranged on the surface of the positive electrode current collector, the positive electrode material layer is arranged on the surface of the first coating away from the positive electrode current collector, the first coating comprises a lithium-containing material and a conductive material, the Dv99 of the lithium-containing material is 500nm to 1000nm, and the specific surface area of the lithium-containing material is 5m 2 / g to 50m 2 / g. The present application provides a first coating on the positive electrode sheet and regulates the Dv99 and specific surface area of the lithium-containing material within the above range, thereby reducing the short-circuit points caused by the contact between the positive electrode sheet and the negative electrode sheet in the nail penetration test, increasing the short-circuit resistance when the electrochemical device is short-circuited, reducing the heat generation power when the short circuit occurs, improving the contact between the positive electrode collector and the first coating and the positive electrode material layer, promoting the transmission of electrons in the positive electrode sheet, and thus improving the safety performance and cycle performance of the electrochemical device.
[0007] In one embodiment of the present application, the Dv99 of the lithium-containing material is 500nm to 700nm. When the Dv99 of the lithium-containing material is within the above range, it is beneficial to further improve the safety performance and cycle performance of the electrochemical device.
[0008] In one embodiment of the present application, the specific surface area of the lithium-containing material is 30 m 2 / g to 50m 2 When the specific surface area of the lithium-containing material is within the above range, it is beneficial to further improve the safety performance and cycle performance of the electrochemical device.
[0009] In one embodiment of the present application, the lithium-containing material satisfies at least one of the following conditions: (1) the Dv50 of the lithium-containing material is 50 nm to 200 nm; (2) the powder resistivity of the lithium-containing material is 50 Ω·cm to 100 Ω·cm. The lithium-containing material satisfies the above characteristics, which is conducive to improving the safety performance and cycle performance of the electrochemical device.
[0010] In one embodiment of the present application, the lithium-containing material includes at least one of lithium iron phosphate, lithium cobalt oxide, lithium iron manganese phosphate or lithium silicate; based on the mass of the first coating, the mass percentage of the lithium-containing material is 50% to 70%. Selecting the above lithium-containing material and regulating its mass percentage within the scope of the present application is more conducive to replenishing the active lithium lost due to the formation of the solid electrolyte interface film (SEI film) during the first charge and discharge process and the active lithium consumed during the cycle process, improving the first coulomb efficiency and energy density of the electrochemical device, reducing the cycle capacity attenuation, and at the same time, it is also conducive to forming a more dense and uniform first coating on the surface of the positive electrode current collector, enhancing the protection of the positive electrode current collector during the nail penetration test, thereby helping to improve the safety performance and cycle performance of the electrochemical device.
[0011] In one embodiment of the present application, the conductive material includes at least one of SnO2, In2O3, CoO, TiO2 or Cr2O3; based on the mass of the first coating, the mass percentage of the conductive material is 20% to 45%. Selecting the above conductive material and regulating its mass percentage within the scope of the present application is conducive to forming a uniform conductive network between the positive electrode material layer and the positive electrode current collector, improving the transmission of electrons in the positive electrode sheet, and reducing the interface contact impedance during the cycle, thereby helping to improve the safety performance and cycle performance of the electrochemical device.
[0012] In one embodiment of the present application, the conductive material further includes a doping element, and the doping element includes at least one of Sb, F or B; based on the mass of the conductive material, the mass percentage of the doping element is 0.5% to 5%. The conductive material includes the above-mentioned doping element and regulates its mass percentage within the scope of the present application. The first coating can protect the positive electrode current collector and reduce the powder resistivity of the conductive material, which is more conducive to forming a uniform conductive network between the positive electrode material layer and the positive electrode current collector, improving the transmission of electrons in the positive electrode sheet, thereby facilitating the improvement of the safety performance and cycle performance of the electrochemical device.
[0013] In one embodiment of the present application, the mass percentage of the doping element is 0.5% to 2% based on the mass of the conductive material. By regulating the mass percentage of the doping element in the conductive material within the above range, the first coating can protect the positive electrode current collector, and is also beneficial to reduce the powder resistivity of the conductive material and improve the transmission of electrons in the positive electrode sheet, thereby further improving the safety performance and cycle performance of the electrochemical device.
[0014] In one embodiment of the present application, the conductive material satisfies at least one of the following conditions: (1) the Dv50 of the conductive material is 50 nm to 200 nm; (2) the powder resistivity of the conductive material is 5 Ω·cm to 20 Ω·cm. The conductive material satisfies the above characteristics, which is conducive to improving the safety performance and cycle performance of the electrochemical device.
[0015] In one embodiment of the present application, the first coating layer further includes a first binder, and the first binder includes a water-soluble metal salt compound; based on the mass of the first coating layer, the mass percentage of the first binder is 5% to 10%. The first binder is selected from the above materials and the mass percentage is within the scope of the present application, which is beneficial to the transmission of electrons and ions in the positive electrode sheet, improves the kinetic performance of the electrochemical device, and improves the tensile strength of the first coating layer. The strong interaction between the first coating layer and the positive current collector is also beneficial to improving the bonding force between the first coating layer and the positive current collector and the cohesive force of the first coating layer, thereby improving the safety performance and cycle performance of the electrochemical device.
[0016] In one embodiment of the present application, the water-soluble metal salt compound includes an alkali metal polyacrylate and / or an alkaline earth metal polyacrylate, the alkali metal polyacrylate includes at least one of sodium polyacrylate, lithium polyacrylate or potassium polyacrylate, and the alkaline earth metal polyacrylate includes at least one of calcium polyacrylate or magnesium polyacrylate. The use of the above-mentioned water-soluble metal salt compounds is more conducive to improving the transmission of electrons and ions in the positive electrode sheet, improving the kinetic performance of the electrochemical device, improving the tensile strength of the first coating, and interacting with the positive current collector to increase the bonding force between the first coating and the positive current collector and the cohesive force of the first coating, thereby further improving the safety performance and cycle performance of the electrochemical device.
[0017] In one embodiment of the present application, the thickness of the first coating is 0.5 μm to 2 μm, and the porosity of the first coating is 10% to 20%. When the thickness and porosity of the first coating are within the scope of the present application, the first coating is relatively dense and uniform, has high mechanical strength, can protect the positive electrode collector during the nail penetration test, reduce the occurrence of short circuits in the electrochemical device, and reduce the probability of thermal runaway caused by local overheating of the electrochemical device. At the same time, the positive electrode sheet has a lower resistance, which is conducive to the transmission of electrons in the positive electrode sheet, thereby facilitating the electrochemical device to have a high volume energy density while improving its safety performance and cycle performance.
[0018] In one embodiment of the present application, the thickness of the first coating layer is 0.5 μm to 1 μm. When the thickness of the first coating layer is within the range of the present application, it is more conducive to improving the volume energy density of the electrochemical device and reducing the resistance of the positive electrode sheet. At the same time, the electrochemical device also has good safety performance and cycle performance.
[0019] In one embodiment of the present application, the bonding force between the first coating and the positive electrode current collector is 500N / m to 2000N / m. When the bonding force between the first coating and the positive electrode current collector is within the scope of the present application, the bonding between the first coating and the positive electrode current collector is good, which can reduce the occurrence of short circuits in the electrochemical device, alleviate the deformation of the positive electrode current collector during the cycle, improve the contact between the positive electrode current collector and the first coating and the positive electrode material layer, and facilitate the transmission of electrons in the positive electrode sheet, thereby facilitating the improvement of the safety performance and cycle performance of the electrochemical device.
[0020] In one embodiment of the present application, the bonding force between the first coating and the positive electrode current collector is 500N / m to 1000N / m. When the bonding force between the first coating and the positive electrode current collector is within the range of the present application, it is beneficial to improve the safety performance and cycle performance of the electrochemical device.
[0021] The second aspect of the present application provides an electrochemical device, the electrochemical device comprising the positive electrode sheet in any of the above embodiments. The electrochemical device of the present application has good safety performance and cycle performance.
[0022] The third aspect of the present application provides an electronic device, which includes the electrochemical device in any of the above embodiments. The electronic device of the present application has a long service life and good performance.
[0023] Beneficial effects of this application:
[0024] The present application provides a positive electrode sheet, an electrochemical device and an electronic device. The positive electrode sheet includes a positive electrode current collector, a first coating and a positive electrode material layer, the first coating is arranged on the surface of the positive electrode current collector, the positive electrode material layer is arranged on the surface of the first coating away from the positive electrode current collector, the first coating includes a lithium-containing material and a conductive material, the Dv99 of the lithium-containing material is 500nm to 1000nm, and the specific surface area of the lithium-containing material is 5m 2 / g to 50m 2 / g. The present application provides a first coating on the positive electrode sheet and regulates the Dv99 and specific surface area of the lithium-containing material within the above range, thereby reducing the short-circuit points caused by the contact between the positive electrode sheet and the negative electrode sheet in the nail penetration test, increasing the short-circuit resistance when the electrochemical device is short-circuited, reducing the heat generation power when the short circuit occurs, improving the contact between the positive electrode collector and the first coating and the positive electrode material layer, promoting the transmission of electrons in the positive electrode sheet, and thus improving the safety performance and cycle performance of the electrochemical device.
[0025] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.
[0027] Figure 1 This is a schematic diagram of the structure of a positive electrode sheet along its thickness direction according to an implementation scheme of the present application.
[0028] Reference numerals: positive electrode current collector 11 , first coating layer 12 , positive electrode material layer 13 . DETAILED DESCRIPTION
[0029] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.
[0030] It should be noted that in the specific embodiments of the present application, a lithium-ion battery is used as an example of an electrochemical device to explain the present application, but the electrochemical device of the present application is not limited to a lithium-ion battery.
[0031] The first aspect of the present application provides a positive electrode plate, the positive electrode plate comprises a positive electrode current collector, a first coating and a positive electrode material layer, the first coating is arranged on the surface of the positive electrode current collector, the positive electrode material layer is arranged on the surface of the first coating away from the positive electrode current collector, and the first coating comprises a lithium-containing material and a conductive material. The Dv99 of the lithium-containing material is 500nm to 1000nm, preferably 500nm to 700nm; the specific surface area of the lithium-containing material is 5m 2 / g to 50m 2 / g, preferably 30m 2 / g to 50m 2 / g. For example, the Dv99 of the lithium-containing material can be 500nm, 550nm, 600nm, 650nm, 700nm, 750nm, 800nm, 850nm, 900nm, 950nm, 1000nm or a range consisting of any two of these values; the specific surface area of the lithium-containing material can be 5m 2 / g, 10m 2 / g, 15m 2 / g, 20m 2 / g, 25m 2 / g, 30m 2 / g, 35m 2 / g, 40m 2 / g, 45m 2 / g, 50m 2 / g or a range consisting of any two values therein.
[0032] The positive electrode sheet of the present application is provided with a first coating, which can reduce the short-circuit points caused by contact between the positive electrode sheet and the negative electrode sheet in the nail penetration test, increase the short-circuit resistance when the electrochemical device is short-circuited, reduce the heat generation power during the short circuit, and can also reduce the deformation of the positive current collector caused by the increase in the volume of the positive electrode sheet due to the phase change of the positive active material, improve the contact between the positive current collector and the first coating and the positive material layer, promote the transmission of electrons in the positive electrode sheet, thereby improving the safety performance and cycle performance of the electrochemical device. The conductive material included in the first coating has good dispersibility and stability in the first coating slurry, which is conducive to uniform distribution in the first coating, thereby forming a uniform conductive network between the positive material layer and the positive current collector, improving the transmission of electrons in the positive electrode sheet, reducing the interface contact impedance during the cycle process, and thus improving the cycle performance of the electrochemical device.
[0033] The first coating includes a lithium-containing material and the Dv99 and specific surface area of the lithium-containing material are regulated within the scope of the present application. The lithium-containing material can serve as a lithium source to supplement the active lithium lost due to the formation of a solid electrolyte interface film (SEI film) during the first charge and discharge process and the active lithium consumed during the cycle, thereby improving the first coulombic efficiency and energy density of the electrochemical device, reducing the cycle capacity attenuation, and improving the cycle performance; the lithium-containing material with a smaller particle size and a larger specific surface area can also form a denser and more uniform first coating on the surface of the positive electrode collector, further enhancing the protective effect on the positive electrode collector during the nail penetration test, wrapping the metal burrs that may be generated by the positive electrode collector during the nail penetration test, reducing the occurrence of short circuits in the electrochemical device, and reducing the probability of thermal runaway caused by local overheating of the electrochemical device, thereby further improving the safety performance of the electrochemical device.
[0034] When the Dv99 of the lithium-containing material is greater than 1000nm, the lithium-containing material with too large a particle size is easy to puncture the positive electrode current collector in the nail penetration test. At the same time, the density of the first coating is too poor, and the protection effect on the positive electrode current collector is poor. The probability of short circuit in the electrochemical device increases, thereby affecting the safety performance of the electrochemical device. When the Dv99 of the lithium-containing material is less than 500nm, the lithium-containing material is easy to agglomerate in the first coating slurry, resulting in poor uniformity of the first coating. In addition, the contact area between the first coating and the electrolyte is too large, and there are too many side reactions between the positive electrode plate and the electrolyte, thereby affecting the cycle performance of the electrochemical device. When the specific surface area of the lithium-containing material is greater than 50m 2 / g, the particle size of the lithium-containing material is too small, and it is easy to agglomerate in the first coating slurry, resulting in poor uniformity of the first coating. In addition, the contact area between the first coating and the electrolyte is too large, and there are too many side reactions between the positive electrode and the electrolyte, thereby affecting the cycle performance of the electrochemical device. When the specific surface area of the lithium-containing material is less than 5m 2 / g, the particle size of the lithium-containing material is too large, which can easily puncture the positive electrode current collector in the nail penetration test. At the same time, the density of the first coating is too poor, which has a poor protective effect on the positive electrode current collector, and the probability of short circuit in the electrochemical device is increased, thereby affecting the safety performance of the electrochemical device.
[0035] Therefore, the present application can form a more compact and mechanically strong first coating on the surface of the positive electrode current collector by setting a first coating on the positive electrode plate and adjusting the Dv99 and specific surface area of the lithium-containing material within the above range, thereby enhancing the protection of the positive electrode current collector and improving the safety performance and cycle performance of the electrochemical device. In the present application, at least part of the surface of the lithium-containing material can be coated with carbon.
[0036] In this application, the above-mentioned “the first coating is disposed on the surface of the positive electrode current collector” means that the first coating can be disposed on one surface of the positive electrode current collector along its own thickness direction, or on two surfaces of the positive electrode current collector along its own thickness direction. It should be noted that the “surface” here can be the entire area of the positive electrode current collector, or it can be a partial area of the positive electrode current collector. This application has no special restrictions, as long as the purpose of this application can be achieved. Specifically, if Figure 1 As shown, a first coating layer 12 and a positive electrode material layer 13 are sequentially stacked on the two surfaces of the positive electrode current collector 11. The above-mentioned "the positive electrode material layer is arranged on the surface of the first coating layer away from the positive electrode current collector" can be understood by analogy, and the positive electrode material layer can be arranged in the entire area of the first coating layer, and can also be arranged in a partial area of the first coating layer.
[0037] In one embodiment of the present application, the Dv50 of the lithium-containing material is 50nm to 200nm. For example, the Dv50 of the lithium-containing material can be 50nm, 70nm, 80nm, 100nm, 120nm, 150nm, 180nm, 200nm or a range composed of any two of the values. When the Dv50 of the lithium-containing material is within the scope of the present application, the lithium-containing material with nanometer particle size can be used as a lithium source to supplement the active lithium lost due to the formation of the SEI film during the first charge and discharge process and the active lithium consumed during the cycle process, improve the first coulomb efficiency and energy density of the electrochemical device, reduce the cycle capacity attenuation, and can also form a more dense and uniform first coating on the surface of the positive electrode collector, further enhance the protective effect on the positive electrode collector during the nail penetration test, wrap the metal burrs that may be generated by the positive electrode collector in the nail penetration test, reduce the occurrence of short circuits in the electrochemical device, and reduce the probability of thermal runaway caused by local overheating of the electrochemical device, thereby helping to improve the safety performance and cycle performance of the electrochemical device.
[0038] In one embodiment of the present application, the powder resistivity of the lithium-containing material is 50Ω·cm to 100Ω·cm. For example, the powder resistivity of the lithium-containing material can be 50Ω·cm, 60Ω·cm, 70Ω·cm, 80Ω·cm, 90Ω·cm, 100Ω·cm, or a range consisting of any two of these values. When the powder resistivity of the lithium-containing material is within the range of the present application, it is beneficial to form a uniform conductive network between the positive electrode material layer and the positive electrode current collector, while increasing the short-circuit resistance when the electrochemical device is short-circuited, reducing the heat generation power during short-circuiting, and reducing the occurrence of short circuits in the electrochemical device, thereby helping to improve the safety performance and cycle performance of the electrochemical device.
[0039] In one embodiment of the present application, the lithium-containing material includes lithium iron phosphate (LiFePO4), lithium cobalt oxide (LiCoO2), lithium iron manganese phosphate (LiMn x Fe 1-x PO4, 0.2≤x≤0.7) or at least one of lithium silicate (Li2SiO3); based on the mass of the first coating, the mass percentage of the lithium-containing material is 50% to 70%. For example, the mass percentage of the lithium-containing material can be 50%, 52%, 54%, 56%, 58%, 60%, 62%, 64%, 66%, 68%, 70% or a range consisting of any two of these values. Selecting the above-mentioned lithium-containing material and regulating its mass percentage within the scope of this application is more conducive to replenishing the active lithium lost due to the formation of the SEI film during the first charge and discharge process and the active lithium consumed during the cycle process, improving the first coulomb efficiency and energy density of the electrochemical device, reducing the cycle capacity attenuation, and at the same time, it is also conducive to forming a more dense and uniform first coating on the surface of the positive current collector, enhancing the protection of the positive current collector during the nail penetration test, thereby helping to improve the safety performance and cycle performance of the electrochemical device.
[0040] In one embodiment of the present application, the conductive material includes at least one of SnO2, In2O3, CoO, TiO2 or Cr2O3; based on the mass of the first coating, the mass percentage of the conductive material is 20% to 45%. For example, the mass percentage of the conductive material can be 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40%, 45% or a range consisting of any two of these values. Selecting the above conductive materials and regulating their mass percentage within the scope of the present application is conducive to forming a uniform conductive network between the positive electrode material layer and the positive electrode current collector, improving the transmission of electrons in the positive electrode sheet, and reducing the interfacial contact impedance during the cycle, thereby helping to improve the safety performance and cycle performance of the electrochemical device.
[0041] In one embodiment of the present application, the conductive material further includes a doping element, and the doping element includes at least one of Sb, F or B; based on the mass of the conductive material, the mass percentage of the doping element is 0.5% to 5%, preferably 0.5% to 2%. For example, the mass percentage of the doping element can be 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% or a range consisting of any two of the values. Generally, the greater the mass percentage of the doping element, the higher the preparation cost of the conductive material, and the smaller the powder resistivity, the application of the first coating will reduce the short-circuit resistance of the electrochemical device when a short circuit occurs, weaken the protective effect on the positive electrode collector, and increase the safety risk. The conductive material includes the above-mentioned doping elements and regulates its mass percentage within the scope of this application. The first coating can protect the positive electrode current collector and can also reduce the powder resistivity of the conductive material, which is more conducive to forming a uniform conductive network between the positive electrode material layer and the positive electrode current collector, improving the transmission of electrons in the positive electrode plate, and at the same time making the electrochemical device have a lower preparation cost, thereby facilitating improving the safety performance and cycle performance of the electrochemical device. In this application, the doping elements in the conductive material can be obtained by adding compounds containing doping elements (e.g., chlorides) during the preparation of the conductive material. The mass percentage of the doping elements in the conductive material can be regulated by regulating the amount of the compound containing the doping elements added.
[0042] In one embodiment of the present application, the Dv50 of the conductive material is 50nm to 200nm. For example, the Dv50 of the conductive material can be 50nm, 80nm, 100nm, 120nm, 150nm, 180nm, 200nm or a range consisting of any two of the values. When the Dv50 of the conductive material is within the scope of the present application, the conductive material with a nanometer particle size is conducive to forming a more dense and uniform first coating on the surface of the positive electrode collector, and is also conducive to forming a uniform conductive network between the positive electrode material layer and the positive electrode collector, improving the transmission of electrons in the positive electrode sheet, thereby helping to improve the safety performance and cycle performance of the electrochemical device.
[0043] In one embodiment of the present application, the powder resistivity of the conductive material is 5Ω·cm to 20Ω·cm. For example, the powder resistivity of the conductive material may be 5Ω·cm, 8Ω·cm, 10Ω·cm, 12Ω·cm, 14Ω·cm, 16Ω·cm, 18Ω·cm, 20Ω·cm, or a range consisting of any two values thereof. When the powder resistivity of the conductive material is within the range of the present application, it is beneficial to improve the transmission of electrons in the positive electrode sheet, thereby improving the safety performance and cycle performance of the electrochemical device.
[0044] In one embodiment of the present application, the first coating layer further includes a first binder, and the first binder includes a water-soluble metal salt compound; based on the mass of the first coating layer, the mass percentage of the first binder is 5% to 10%. For example, the mass percentage of the first binder can be 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, or a range consisting of any two of these values. The first binder is selected from the above materials and the mass percentage is within the scope of this application. The water-soluble metal salt compound has good hydrophilicity, and its electronic conductivity and ionic conductivity are better than those of non-water-soluble polymer binders such as polyvinylidene fluoride and polyvinylidene chloride, which is beneficial to the transmission of electrons and ions in the positive electrode plate. Therefore, applying it to the first coating can improve the kinetic performance of the electrochemical device and improve the cycle performance of the electrochemical device. In addition, the water-soluble metal salt compound has a large specific surface area and can be highly dispersed after encountering water. When used as a binder in the first coating, it can improve the tensile strength of the first coating. The strong interaction between the first coating and the positive current collector is also beneficial to enhancing the bonding force between the first coating and the positive current collector and the cohesive force of the first coating, thereby improving the safety performance of the electrochemical device.
[0045] In one embodiment of the present application, the water-soluble metal salt compound includes an alkali metal polyacrylate and / or an alkaline earth metal polyacrylate, the alkali metal polyacrylate includes at least one of sodium polyacrylate, lithium polyacrylate or potassium polyacrylate, and the alkaline earth metal polyacrylate includes at least one of calcium polyacrylate or magnesium polyacrylate. The use of the above-mentioned water-soluble metal salt compounds is more conducive to improving the transmission of electrons and ions in the positive electrode plate, improving the kinetic performance of the electrochemical device, and also conducive to improving the tensile strength of the first coating layer, interacting with the positive current collector to increase the bonding force between the first coating layer and the positive current collector and the cohesive force of the first coating layer, thereby further improving the safety performance and cycle performance of the electrochemical device.
[0046] In one embodiment of the present application, the thickness of the first coating is 0.5 μm to 2 μm, preferably 0.5 μm to 1 μm. For example, the thickness of the first coating can be 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2 μm or a range consisting of any two of the values. When the thickness of the first coating is within the scope of the present application, the first coating has a high mechanical strength, can protect the positive electrode collector during the nail penetration test, reduce the occurrence of short circuits in the electrochemical device, and reduce the probability of thermal runaway caused by local overheating of the electrochemical device. At the same time, the positive electrode sheet has a lower resistance, which is conducive to the transmission of electrons in the positive electrode sheet, thereby facilitating the electrochemical device to have a high volume energy density while improving its safety performance and cycle performance.
[0047] In one embodiment of the present application, the porosity of the first coating is 10% to 20%. For example, the porosity of the first coating can be 10%, 12%, 14%, 15%, 16%, 18%, 20% or a range consisting of any two of these values. When the porosity of the first coating is within the scope of the present application, the first coating formed on the surface of the positive electrode current collector is relatively dense and uniform, which can enhance the protection of the positive electrode current collector during the nail penetration test, reduce the occurrence of short circuits in the electrochemical device, and also facilitate the transmission of electrons and ions in the positive electrode sheet, thereby facilitating the improvement of the safety performance and cycle performance of the electrochemical device.
[0048] In one embodiment of the present application, the bonding force between the first coating and the positive electrode current collector is 500N / m to 2000N / m, preferably 500N / m to 1000N / m. For example, the bonding force between the first coating and the positive electrode current collector can be 500N / m, 600N / m, 700N / m, 800N / m, 900N / m, 1000N / m, 1200N / m, 1500N / m, 1800N / m, 2000N / m or a range consisting of any two of these values. Generally, the greater the bonding force between the first coating and the positive electrode current collector, the higher the content of the first binder in the first coating, which affects the dispersibility of the first coating slurry, resulting in poor coating effect, poor uniformity of distribution of the components in the first coating, and affects the safety performance and cycle performance of the electrochemical device. When the bonding force between the first coating and the positive electrode current collector is within the scope of this application, the amount of the first binder in the first coating slurry is relatively small, which can improve the dispersibility of the first coating slurry, achieve a good coating effect, and make the components in the first coating uniformly distributed. At the same time, the bonding between the first coating and the positive electrode current collector is good. The first coating can wrap the metal burrs that may be generated in the positive electrode current collector under abnormal conditions such as nail penetration and impact, reduce the occurrence of short circuits in the electrochemical device, reduce the probability of thermal runaway or overheating combustion of the electrochemical device due to local overheating, and improve the safety performance of the electrochemical device. On the other hand, since the volume of the positive active material in the positive electrode material layer will expand during the cycle, the first coating with a strong bonding force can alleviate the deformation of the positive electrode current collector during the cycle, improve the contact between the positive electrode current collector and the first coating and the positive electrode material layer, which is beneficial to the transmission of electrons in the positive electrode sheet and improves the cycle performance of the electrochemical device.
[0049] The present application has no particular restrictions on the preparation method of the positive electrode sheet, as long as the purpose of the present application can be achieved. For example, the preparation of the positive electrode sheet may include but is not limited to the following steps: mixing the lithium-containing material, the conductive material and the first binder in a mass ratio of (50 to 70): (20 to 45): (5 to 10), adding deionized water as a solvent, and stirring evenly to obtain a first coating slurry with a solid content of 70wt% to 80wt%. Then the first coating slurry is coated on one surface of the positive electrode current collector of 5μm to 20μm, and a first coating with a thickness of 0.5μm to 2μm is obtained after oven drying. Then prepare the positive electrode material layer slurry, coat the positive electrode material layer slurry on the surface of the first coating, dry it, and obtain a positive electrode sheet with a single-sided coating of the first coating and the positive electrode material layer. Repeat the above steps on the other surface of the positive electrode current collector to obtain a positive electrode sheet with a double-sided coating of the first coating and the positive electrode material layer.
[0050] In some embodiments, the conductive material including the doping element can be purchased. In other embodiments, the conductive material including the doping element can be prepared by the following method: TiCl4, SnCl4·5H2O and SbCl3 are dissolved in deionized water respectively, and then the three solutions are mixed, and an appropriate amount of alkali (such as NaOH) is added to adjust the pH value and promote the formation of precipitation. The mixed solution is transferred to an autoclave and reacted at 150°C to 200°C for several hours. After the reaction is completed, the obtained product is filtered, washed and dried. The dried product is calcined at a high temperature of 500°C to 800°C for several hours to form a Sb-doped SnO2-coated TiO2 conductive material. The mass percentage of the doping element in the conductive material can be regulated by regulating the amount of the compound including the doping element during the preparation process.
[0051] In this application, Dv50 means the particle size at which the volume accumulation reaches 50% from the small particle size side in the volume-based particle size distribution of the material; Dv99 means the particle size at which the volume accumulation reaches 99% from the small particle size side in the volume-based particle size distribution of the material. The above-mentioned material may be a lithium-containing material or a conductive material.
[0052] Generally, lithium-containing materials of different particle sizes and specific surface areas and conductive materials of different particle sizes can be obtained by mechanical crushing (such as ball milling). For example, the particle size and specific surface area of lithium-containing materials and the particle size of conductive materials can be regulated by regulating the ball milling time. When other conditions remain unchanged, the Dv50 and Dv99 of lithium-containing materials decrease when the ball milling time is prolonged; the Dv50 and Dv99 of lithium-containing materials increase when the ball milling time is shortened. When other conditions remain unchanged, the specific surface area of lithium-containing materials increases when the ball milling time is prolonged; the specific surface area of lithium-containing materials decreases when the ball milling time is shortened. When other conditions remain unchanged, the Dv50 of conductive materials decreases when the ball milling time is prolonged; the Dv50 of conductive materials increases when the ball milling time is shortened.
[0053] Generally, the resistivity of the powder of the lithium-containing material can be controlled by adjusting the content of the coated carbon. For example, when other conditions remain unchanged, the resistivity of the powder of the lithium-containing material decreases when the content of the coated carbon increases; and the resistivity of the powder of the lithium-containing material increases when the content of the coated carbon decreases.
[0054] Generally, the powder resistivity of the conductive material can be controlled by adjusting the mass percentage of the doping element in the conductive material. For example, when other conditions remain unchanged, the mass percentage of the doping element in the conductive material increases, and the powder resistivity of the conductive material decreases; the mass percentage of the doping element in the conductive material decreases, and the powder resistivity of the conductive material increases.
[0055] Generally, the porosity of the first coating layer can be regulated by regulating the particle sizes of the lithium-containing material and the conductive material. For example, when other conditions remain unchanged, the particle size of the lithium-containing material increases, and the porosity of the first coating layer decreases; when the particle size of the lithium-containing material decreases, the porosity of the first coating layer increases. When other conditions remain unchanged, the particle size of the conductive material increases, and the porosity of the first coating layer decreases; when the particle size of the conductive material decreases, the porosity of the first coating layer increases.
[0056] Generally, the thickness of the first coating layer can be regulated by regulating the single-sided coating weight of the first coating layer. For example, when other conditions remain unchanged, the single-sided coating weight of the first coating layer increases, and the thickness of the first coating layer increases; and the single-sided coating weight of the first coating layer decreases, and the thickness of the first coating layer decreases.
[0057] In the present application, lithium-containing materials with different particle sizes, specific surface areas, and powder resistivities and conductive materials with different particle sizes and powder resistivities can be purchased, and the particle size, specific surface area, and powder resistivity of the lithium-containing materials and the particle size and powder resistivity of the conductive materials can be tested in combination with the "particle size test", "specific surface area test", and "powder resistivity test" test methods provided in the present application, and the lithium-containing materials with the required particle size, specific surface area, and powder resistivity and the conductive materials with the required particle size and powder resistivity can be selected.
[0058] The present application has no particular limitation on the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include aluminum foil, aluminum alloy foil or a composite current collector (such as an aluminum-carbon composite current collector).
[0059] The positive electrode material layer includes a positive electrode active material. The present application has no particular limitation on the positive electrode active material as long as the purpose of the present application can be achieved. For example, the positive electrode active material may include but is not limited to at least one of lithium nickel cobalt manganese oxide (such as NCM811, NCM622, NCM523, NCM111), lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium manganese oxide, lithium iron manganese phosphate or lithium titanate.
[0060] The positive electrode material layer may also include a first conductive agent and a second binder. The present application does not particularly limit the types of the first conductive agent and the second binder, as long as the purpose of the present application can be achieved. For example, the first conductive agent may include but is not limited to at least one of conductive carbon black (Super P), carbon nanotubes (CNTs), carbon fibers, flake graphite, graphene, metal materials or conductive polymers, and the conductive carbon black may include but is not limited to at least one of acetylene black or Ketjen black. The above-mentioned carbon nanotubes may include but are not limited to single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The above-mentioned carbon fibers may include but are not limited to vapor-grown carbon fibers (VGCF) and / or nano-carbon fibers. The above-mentioned metal materials may include but are not limited to metal powders and / or metal fibers. Specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The above-mentioned conductive polymer may include but is not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole. For example, the second binder may include, but is not limited to, at least one of polyacrylic acid, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyvinyl alcohol, carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polyimide, polyamide-imide, styrene-butadiene rubber, or polyvinylidene fluoride. The present application does not particularly limit the mass ratio of the positive electrode active material, the first conductive agent, and the second binder in the positive electrode material layer. Those skilled in the art can select according to actual needs as long as the purpose of the present application can be achieved.
[0061] The present application has no particular restrictions on the thickness of the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, the thickness of the positive electrode current collector is 5 μm to 10 μm. The present application has no particular restrictions on the thickness of the positive electrode material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the positive electrode material layer is 70 μm to 90 μm.
[0062] The second aspect of the present application provides an electrochemical device, which includes the positive electrode plate in any of the aforementioned embodiments. The electrochemical device also includes a negative electrode plate, which includes a negative electrode collector and a negative electrode material layer disposed on at least one surface of the negative electrode collector. The above-mentioned "negative electrode plate includes a negative electrode collector and a negative electrode material layer disposed on at least one surface of the negative electrode collector" means that the negative electrode material layer can be disposed on one surface of the negative electrode collector along the thickness direction of itself, or on two surfaces of the negative electrode collector along the thickness direction of itself. It should be noted that the "surface" here can be the entire area of the surface of the negative electrode collector, or it can be a partial area of the surface of the negative electrode collector. This application is not particularly limited as long as the purpose of this application can be achieved.
[0063] The present application has no particular limitation on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam or a composite current collector. For example, the composite current collector may be a lithium-copper composite current collector, a carbon-copper composite current collector, a nickel-copper composite current collector or a titanium-copper composite current collector, etc.
[0064] The negative electrode material layer includes a negative electrode active material. The present application has no particular limitation on the negative electrode active material as long as the purpose of the present application can be achieved. For example, the negative electrode active material may include but is not limited to natural graphite, artificial graphite, mesophase microcarbon beads, hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 Or at least one of Li-Al alloy.
[0065] In some embodiments of the present application, the negative electrode material layer may further include a second conductive agent and a third binder, for example, it may be at least one of the first conductive agent and the second binder. The present application does not particularly limit the mass ratio of the negative electrode active material, the second conductive agent, and the third binder in the negative electrode material layer, and those skilled in the art may select according to actual needs, as long as the purpose of the present application can be achieved.
[0066] The present application has no particular limitation on the thickness of the negative electrode material layer and the thickness of the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode material layer is 80 μm to 100 μm, and the thickness of the negative electrode current collector is 4 μm to 15 μm.
[0067] Optionally, the negative electrode plate may further include a conductive layer, and the conductive layer is located between the negative electrode current collector and the negative electrode material layer. The present application has no particular restrictions on the composition of the conductive layer, and it may be a conductive layer commonly used in the art. For example, the conductive layer includes a conductive layer conductive agent and a conductive layer binder. The present application has no particular restrictions on the conductive layer conductive agent and the conductive layer binder in the conductive layer, and for example, it may be at least one of the above-mentioned first conductive agent and the above-mentioned second binder.
[0068] In the present application, the electrochemical device also includes an isolation membrane. The present application has no particular restrictions on the isolation membrane, as long as the purpose of the present application can be achieved. For example, the material of the isolation membrane may include but is not limited to polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (e.g., polyethylene terephthalate (PET) membranes), cellulose, polyimide (PI), polyamide (PA), spandex or aramid. The type of isolation membrane may include at least one of a woven membrane, a non-woven membrane, a microporous membrane, a composite membrane, a rolled membrane or a spun membrane.
[0069] In some embodiments of the present application, the isolation film may include a substrate layer and a surface treatment layer. The substrate layer may be a non-woven fabric or a composite film having a porous structure, and the material of the substrate layer may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used.
[0070] Optionally, a surface treatment layer is disposed on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing a polymer and an inorganic layer.
[0071] In some embodiments of the present application, the inorganic layer includes ceramic particles and an inorganic layer binder. The present application has no particular restrictions on ceramic particles, such as ceramic particles can include at least one of silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular restrictions on the inorganic layer binder, such as the inorganic layer binder can be at least one of the above-mentioned second binder. In some embodiments of the present application, the polymer layer includes a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinyl pyrrolidone, polyvinyl ether or polyvinylidene fluoride or poly (vinylidene fluoride-hexafluoropropylene).
[0072] In the present application, there is no particular limitation on the thickness of the isolation film, as long as the purpose of the present application can be achieved. For example, the thickness of the isolation film may be 3 μm to 30 μm.
[0073] In the present application, the electrochemical device further includes an electrolyte, and the electrolyte includes a lithium salt and a non-aqueous solvent.
[0074] The present application has no particular restrictions on lithium salts, as long as the purpose of the present application can be achieved. For example, the lithium salt may include but is not limited to at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, Li2SiF6, lithium bis(oxalatoborate) (LiBOB) or lithium difluoroborate. The present application has no particular restrictions on the content of lithium salts in the electrolyte, as long as the purpose of the present application can be achieved.
[0075] The present application has no particular limitation on the non-aqueous solvent as long as the purpose of the present application can be achieved. For example, the non-aqueous solvent may include but is not limited to at least one of carbonate compounds, carboxylate compounds, ether compounds or other organic solvents.
[0076] The carbonate compound may include but is not limited to at least one of a chain carbonate compound, a cyclic carbonate compound or a fluorinated carbonate compound. The chain carbonate compound may include but is not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or ethyl methyl carbonate (MEC). The cyclic carbonate compound may include but is not limited to at least one of ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC) or vinyl ethylene carbonate (VEC). The fluorinated carbonate compound may include, but is not limited to, at least one of fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, or trifluoromethylethylene carbonate. The above-mentioned carboxylate compound may include, but is not limited to, at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decalactone, valerolactone, or caprolactone. The above-mentioned ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1-ethoxy-1-methoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include but are not limited to at least one of dimethyl sulfoxide, 1,2-dioxolane, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate or trioctyl phosphate. The present application has no particular restrictions on the content of the non-aqueous solvent in the electrolyte, as long as the purpose of the present application can be achieved.
[0077] The electrochemical device also includes a housing for accommodating a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, as well as other components known in the field of electrochemical devices, and this application does not limit the above-mentioned other components. This application does not particularly limit the housing, and it can be a housing known in the art, as long as the purpose of this application can be achieved. For example, the housing can be a hard shell housing or a flexible shell. The material of the hard shell housing can be metal, and this application does not limit the type of metal, and a metal hard shell housing known in the art can be used, as long as the purpose of this application can be achieved. The flexible housing can be a metal plastic film, such as an aluminum plastic film, a steel plastic film, etc.
[0078] The preparation process of the electrochemical device of the present application is well known to those skilled in the art, and the present application has no particular limitations. For example, the preparation process of the electrochemical device may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly with a wound structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain an electrochemical device. Alternatively, stacking the positive electrode sheet, the separator and the negative electrode sheet in order, and then fixing the four corners of the entire stacked structure with tape to obtain an electrode assembly with a stacked structure, placing the electrode assembly in a shell, injecting the electrolyte into the shell and sealing it to obtain an electrochemical device. In addition, overcurrent protection elements, guide plates, etc. may also be placed in the shell as needed to prevent pressure rise and overcharge and discharge inside the electrochemical device.
[0079] The third aspect of the present application provides an electronic device, which includes the electrochemical device in any of the above embodiments. The electronic device of the present application has a long service life and good performance.
[0080] The electronic device of the present application is not particularly limited, and it can be any electronic device known in the prior art. In some embodiments, the electronic device can include but is not limited to a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.
[0081] Example
[0082] Hereinafter, the embodiments of the present application will be described in more detail with reference to Examples and Comparative Examples. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are by mass.
[0083] Test methods and equipment:
[0084] Particle size testing
[0085] The particle size Dv50 and Dv99 of lithium-containing materials and the particle size Dv50 of conductive materials were tested using a Malvern particle size tester (model: MasterSizer 2000). The specific test was conducted in accordance with the national standard GB / T19077-2016 "Laser Diffraction Method for Particle Size Distribution".
[0086] Specific surface area test
[0087] The specific surface area of lithium-containing materials was tested by nitrogen adsorption using a specific surface area analyzer (Tristar II 3020M). The specific test was conducted in accordance with the national standard GB / T 19587-2017 "Determination of the specific surface area of solid substances by gas adsorption BET method".
[0088] Powder resistivity test
[0089] The lithium-containing material powder sample or the conductive material powder sample is evenly compacted in a mold to form a cylindrical sample with a flat surface. The resistivity of the sample is tested using the four-probe method. Four probes arranged in a straight line are installed on the sample, two of which are current probes for injecting current into the sample, and the other two are voltage probes for measuring the voltage drop caused by the current passing through the sample. The voltage probe is located in the center of the sample. A constant DC current is applied to the sample through the current probe. When the current passes through the sample, the voltage drop across the sample is measured using a voltage probe. According to Ohm's law, the resistance R of the sample is calculated by the measured current and voltage values. Then, using the geometric dimensions of the sample, the resistivity of the sample is calculated by the following formula: resistivity = (resistance × cross-sectional area) / length, where for cylindrical samples, the cross-sectional area refers to the area of the bottom circle, and the length refers to the height of the cylindrical sample. Measure 3 times and take the average value as the powder resistivity of the lithium-containing material or the powder resistivity of the conductive material.
[0090] Thickness test
[0091] The lithium-ion battery was discharged at a constant current of 0.1C to 3.0V, and the lithium-ion battery was disassembled to obtain the positive electrode sheet. The positive electrode sheet was cleaned with dimethyl carbonate (DMC) for 10 minutes, and then the positive electrode sheet was baked at 100°C for 2 hours for standby use. The positive electrode sheet was cut and the cross section of the positive electrode sheet along the thickness direction was polished with argon ions. Then, a scanning electron microscope (OXFORD·EDS) was used to observe and measure the thickness of the first coating at three locations, and the average value was taken as the thickness of the first coating.
[0092] Porosity test
[0093] The lithium-ion battery was discharged at a constant current of 0.1C to 3.0V, and the lithium-ion battery was disassembled to obtain the positive electrode plate, which was cleaned with dimethyl carbonate (DMC) for 10 minutes, and then baked at 100°C for 2 hours for standby use. The positive electrode material layer was scraped off to obtain a positive electrode current collector with a first coating on the surface. The porosity of the first coating was tested by mercury intrusion using a porosity analysis tester. Among them, the specific test of porosity was carried out in accordance with the national standard GB / T 21650.1-2008 "Determination of pore size distribution and porosity of solid materials by mercury intrusion and gas adsorption method Part 1: Mercury intrusion method".
[0094] Adhesion test
[0095] Take the positive electrode sheet coated only with the first coating, stick the positive electrode sheet on a smooth steel plate with double-sided tape, stick the other side of the positive electrode sheet with tape, and fix one end of the tape on the tensile testing machine. Set the speed to 10 mm / min, and start pulling the tape straight at 180° with the tensile testing machine. Read the bonding force of the tape when it is stretched, export the data and divide it by the width of the tape to get the bonding force between the first coating and the positive current collector.
[0096] Cyclic performance test
[0097] After the lithium-ion battery is left to stand for 30 minutes in an environment of 45℃±3℃, it is charged to 4.25V at a constant current of 1.25C, then charged to 4.5V at a constant current of 1.5C, then charged to 0.05C at a constant voltage of 4.5V, left to stand for 30 minutes, and then discharged to 3.0V at a constant current of 0.7C. The discharge capacity obtained in this step is the initial capacity. Repeat the above cycle, and the discharge capacity of each cycle is compared with the initial capacity to obtain the discharge capacity retention rate of each cycle, and record the number of cycles of the lithium-ion battery at 45℃±3℃ until the discharge capacity retention rate is 80%. The cycle performance of the lithium-ion battery is characterized by the number of cycles at 45℃±3℃ until the capacity retention rate is 80%. The higher the number of cycles of the lithium-ion battery at 45℃±3℃ until the capacity retention rate is 80%, the better the cycle performance of the lithium-ion battery.
[0098] Nail penetration test
[0099] Take 10 lithium-ion batteries in each embodiment and comparative example, and fully charge them at 25±3°C. The specific steps are: charge at a constant current of 0.5C to 4.5V, and then charge at a constant voltage of 4.5V to a current cutoff of 0.05C.
[0100] The lithium-ion battery was subjected to a nail penetration test at 25±3℃, using a steel nail with a diameter of 4mm, made of carbon steel, with a taper of 16.5mm, and a total length of 100mm. The nail penetration speed was set to 30mm / s, and the nail penetration depth was based on the taper of the steel nail passing through the lithium-ion battery. The state of the lithium-ion battery was observed during the test, and the lithium-ion battery was judged as passing the nail penetration test based on the criterion of not burning or exploding. The number of lithium-ion batteries that passed the nail penetration test was recorded. The safety performance of lithium-ion batteries is characterized by the pass rate of the nail penetration test. The higher the pass rate of the nail penetration test, the better the safety performance of the lithium-ion battery.
[0101] Example 1
[0102] <Preparation of positive electrode sheet>
[0103] The lithium-containing material lithium iron phosphate, the ball-milled conductive material SnO2 (AM-SnO2-028-2, provided by Zhejiang Yamei Nano Technology Co., Ltd.) and the first binder sodium polyacrylate were mixed in a mass ratio of 60:32:8, deionized water was added as a solvent, and the mixture was stirred evenly to obtain a first coating slurry with a solid content of 75wt%, which was coated on one surface of an 8μm positive electrode current collector aluminum foil, and after oven drying, a first coating with a thickness of 1μm was obtained. The positive electrode active material lithium cobalt oxide, the first conductive agent conductive carbon black, and the second binder polyvinylidene fluoride were mixed in a mass ratio of 97.3:1.1:1.6, N-methylpyrrolidone (NMP) was added as a solvent, and the mixture was stirred evenly in a vacuum mixer to obtain a positive electrode material layer slurry with a solid content of 75wt%. The positive electrode material layer slurry is evenly coated on the surface of the first coating layer and dried at 120°C to obtain a positive electrode sheet coated with the first coating layer and the positive electrode material layer on one side. The single-side coating weight of the positive electrode material layer is 267.8 mg / 1540 mm 2 . Then repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet coated with the first coating and the positive electrode material layer on both sides. Then, after cold pressing, cutting, and welding the pole ears, a positive electrode sheet with a specification of 74mm×867mm is obtained for standby use. Among them, the thickness of the single-sided positive electrode material layer is 80μm, and the Dv50, Dv99, specific surface area, and powder resistivity of the lithium-containing material, the Dv50 and powder resistivity of the conductive material, and the porosity of the first coating are shown in Table 1.
[0104] <Preparation of negative electrode sheet>
[0105] The negative electrode active material artificial graphite, the third binder styrene butadiene rubber (SBR) and carboxymethyl cellulose (CMC) were mixed at a mass ratio of 97.7:1:1.3, and then deionized water was added as a solvent to prepare a slurry with a solid content of 70wt%. The negative electrode slurry was obtained after being stirred evenly by a vacuum mixer. The negative electrode slurry was evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 6μm, and dried at 120°C to obtain a negative electrode sheet with a single-sided coating of a negative electrode material layer. The single-sided coating weight of the negative electrode material layer was 142mg / 1540mm 2 Then repeat the above steps on the other surface of the copper foil to obtain a negative electrode sheet with a negative electrode material layer coated on both sides. After drying at 120°C, cold pressing, cutting and welding the tabs, a negative electrode sheet with a specification of 78mm×875mm is obtained for standby use. The thickness of the single-sided negative electrode material layer is 85μm.
[0106] <Preparation of Electrolyte>
[0107] In an argon atmosphere glove box with a water content of less than 10ppm, carbonate compounds ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) were uniformly mixed at a mass ratio of 10:30:60 to obtain a basic solvent, and lithium salt LiPF6 was added and stirred evenly to obtain an electrolyte. Among them, based on the total mass of the electrolyte, the mass percentage of lithium salt LiPF6 is 12.5%, and the remainder is the basic solvent.
[0108] <Isolation film>
[0109] A polyethylene porous polymer film with a thickness of 8 μm (manufacturer: Celgard Membrane Co., Ltd., USA) was used as a separator.
[0110] <Preparation of lithium-ion batteries>
[0111] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and the electrode assembly is wound up, the electrode assembly is packed into an aluminum-plastic film packaging bag, and the moisture is removed at 80°C, the prepared electrolyte is injected, and the lithium-ion battery is obtained through vacuum packaging, standing, forming, and shaping processes, wherein the upper limit voltage of the formation is 4.53V, the formation temperature is 85°C, and the formation time is 45min to 60min.
[0112] Example 2 to Example 25
[0113] Except for adjusting the corresponding preparation parameters according to Table 1, the rest is the same as Example 1. Among them, the Dv50, Dv99 and specific surface area of the lithium-containing material are regulated by adjusting the ball milling time of the lithium-containing material, the Dv50 of the conductive material is regulated by adjusting the ball milling time of the conductive material, the thickness of the first coating layer is regulated by adjusting the single-sided coating weight of the first coating layer, and the powder resistivity of the lithium-containing material is regulated by adjusting the content of the coated carbon.
[0114] Embodiment 26
[0115] Except for selecting the conductive material including doping elements that has been ball-milled (AM-ATO-038-2, provided by Zhejiang Yamei Nanotechnology Co., Ltd.) in <Preparation of the positive electrode sheet>, the rest is the same as Example 1.
[0116] Example 27 to Example 32
[0117] Except for adjusting the corresponding preparation parameters according to Table 1, the rest is the same as Example 26.
[0118] Comparative Example 1 to Comparative Example 2
[0119] Except for adjusting the corresponding preparation parameters according to Table 1, the rest is the same as Example 1. The Dv50, Dv99 and specific surface area of the lithium-containing material are regulated by regulating the ball milling time of the lithium-containing material.
[0120] Comparative Example 3 to Comparative Example 4
[0121] Except for adjusting the corresponding preparation parameters according to Table 1, the rest is the same as Example 28. The Dv50, Dv99 and specific surface area of the lithium-containing material are regulated by regulating the ball milling time of the lithium-containing material.
[0122] Comparative Example 5
[0123] Except that the following preparation method is used for <Preparation of the positive electrode sheet>, the rest is the same as Example 1.
[0124] <Preparation of positive electrode sheet>
[0125] The positive electrode active material lithium cobalt oxide, the first conductive agent conductive carbon black, and the second binder polyvinylidene fluoride were mixed in a mass ratio of 97.3:1.1:1.6, N-methylpyrrolidone (NMP) was added as a solvent, and the vacuum mixer was stirred to obtain a positive electrode material layer slurry with a solid content of 75wt%. The positive electrode material layer slurry was evenly coated on one surface of an 8μm positive electrode current collector aluminum foil, and dried at 120°C to obtain a positive electrode sheet coated with a single-sided positive electrode material layer. The single-sided coating weight of the positive electrode material layer was 267.8mg / 1540mm 2 Then repeat the above steps on the other surface of the aluminum foil, and after drying at 120°C, a positive electrode sheet coated with a positive electrode material layer on both sides is obtained. Then, after cold pressing, cutting, and welding the tabs, a positive electrode sheet with a specification of 74mm×867mm is obtained for standby use. Among them, the thickness of the single-sided positive electrode material layer is 80μm.
[0126] Comparative Example 6 to Comparative Example 7
[0127] Except for adjusting the corresponding preparation parameters according to Table 1, the rest is the same as Example 1.
[0128] The preparation parameters and performance parameters of each embodiment and comparative example are shown in Table 1.
[0129] Table 1
[0130] Note: “ / ” in Table 1 means there is no corresponding parameter.
[0131] It can be seen from Examples 1 to 32 and Comparative Examples 1 to 7 that when the positive electrode plate has the first coating structure of the present application and the Dv99 and specific surface area of the lithium-containing material are regulated within the range of the present application, the bonding force between the first coating and the positive electrode collector is high, and the lithium-ion battery prepared using the above-mentioned positive electrode plate has a high number of cycles at 45°C until the capacity retention rate is 80%, and a high pass rate in the nail penetration test, indicating that the lithium-ion battery of the present application has good cycle performance and safety performance. However, the Dv99 and specific surface area of the lithium-containing material in the positive electrode sheet of the lithium-ion batteries of Comparative Examples 1 to 4 are not within the scope of the present application. The positive electrode sheet of the lithium-ion battery of Comparative Example 5 does not include the first coating. The specific surface area of the lithium-containing material in the positive electrode sheet of the lithium-ion battery of Comparative Example 6 is not within the scope of the present application. The Dv99 of the lithium-containing material in the positive electrode sheet of the lithium-ion battery of Comparative Example 7 is not within the scope of the present application. The lithium-ion batteries of Comparative Examples 1 to 7 have a low number of cycles at 45°C until the capacity retention rate is 80%, or a low pass rate in the nail penetration test, indicating that the lithium-ion batteries cannot have good cycle performance and safety performance at the same time.
[0132] The Dv99 and specific surface area of lithium-containing materials usually affect the cycle performance and safety performance of lithium-ion batteries. It can be seen from Examples 1 to 5, Examples 26 to 30, Comparative Examples 1 to 4, Comparative Examples 6 and Comparative Examples 7 that when the Dv99 and specific surface area of the lithium-containing material are within the scope of this application, the bonding force between the first coating and the positive electrode current collector is high, and the prepared lithium-ion battery has a high number of cycles and a nail penetration test pass rate at 45°C until the capacity retention rate is 80%, indicating that the lithium-ion battery of this application has good cycle performance and safety performance. However, the Dv99 and / or specific surface area of the lithium-containing material in Comparative Examples 1 to 4, Comparative Examples 6 and Comparative Examples 7 are not within the scope of this application, and the prepared lithium-ion battery has a low number of cycles or a nail penetration test pass rate at 45°C until the capacity retention rate is 80%, indicating that the lithium-ion battery cannot have good cycle performance and safety performance at the same time.
[0133] The Dv50 of lithium-containing materials usually affects the cycle performance and safety performance of lithium-ion batteries. It can be seen from Examples 1 to 5 that when the Dv50 of the lithium-containing material is within the range of this application, the bonding force between the first coating and the positive electrode current collector is high, and the number of cycles and nail penetration test pass rate of the prepared lithium-ion battery at 45°C until the capacity retention rate is 80% are high, indicating that the lithium-ion battery of this application has good cycle performance and safety performance.
[0134] The Dv50 of the conductive material usually affects the cycle performance and safety performance of the lithium-ion battery. It can be seen from Examples 1, 6 to 10 that when the Dv50 of the conductive material is within the range of this application, the bonding force between the first coating and the positive electrode current collector is high, and the number of cycles and nail penetration test pass rate of the prepared lithium-ion battery at 45°C until the capacity retention rate is 80% are high, indicating that the lithium-ion battery of this application has good cycle performance and safety performance.
[0135] The thickness of the first coating layer usually affects the cycle performance and safety performance of the lithium-ion battery. It can be seen from Examples 1 and 15 to 19 that when the thickness of the first coating layer is within the range of the present application, the bonding force between the first coating layer and the positive electrode current collector is high, and the number of cycles of the prepared lithium-ion battery cycled to 80% of the capacity retention rate at 45°C and the nail penetration test pass rate are high, indicating that the lithium-ion battery of the present application has good cycle performance and safety performance.
[0136] The porosity of the first coating layer usually affects the cycle performance and safety performance of the lithium-ion battery. It can be seen from Examples 1 to 10 that when the porosity of the first coating layer is within the range of the present application, the bonding force between the first coating layer and the positive electrode current collector is high, and the number of cycles and the nail penetration test pass rate of the prepared lithium-ion battery at 45°C until the capacity retention rate is 80% are high, indicating that the lithium-ion battery of the present application has good cycle performance and safety performance.
[0137] The powder resistivity of lithium-containing materials usually affects the cycle performance and safety performance of lithium-ion batteries. It can be seen from Examples 1 and 20 to 23 that when the powder resistivity of the lithium-containing material is within the range of this application, the bonding force between the first coating and the positive electrode current collector is high, and the number of cycles and nail penetration test pass rate of the prepared lithium-ion battery at 45°C until the capacity retention rate is 80% are high, indicating that the lithium-ion battery of this application has good cycle performance and safety performance.
[0138] The powder resistivity of the conductive material usually affects the cycle performance and safety performance of the lithium-ion battery. It can be seen from Examples 1 and 26 to 32 that when the powder resistivity of the conductive material is within the range of the present application, the bonding force between the first coating and the positive electrode current collector is high, and the number of cycles of the prepared lithium-ion battery at 45°C until the capacity retention rate is 80% and the pass rate of the nail penetration test are high, indicating that the lithium-ion battery of the present application has good cycle performance and safety performance.
[0139] The type and mass percentage of the doping element in the conductive material usually affect the cycle performance and safety performance of the lithium-ion battery. It can be seen from Examples 1 and 26 to 32 that when the type and mass percentage of the doping element in the conductive material are within the scope of this application, the bonding force between the first coating and the positive electrode current collector is high, and the number of cycles and nail penetration test pass rate of the prepared lithium-ion battery at 45°C until the capacity retention rate is 80% are high, indicating that the lithium-ion battery of this application has good cycle performance and safety performance.
[0140] The types and mass percentages of the lithium-containing material, the conductive material, and the first binder usually affect the cycle performance and safety performance of the lithium-ion battery. From Examples 1 to 32, it can be seen that when the types and mass percentages of the lithium-containing material, the conductive material, and the first binder are within the scope of this application, the bonding force between the first coating and the positive electrode current collector is high, and the number of cycles and nail penetration test pass rate of the prepared lithium-ion battery at 45°C until the capacity retention rate is 80% are high, indicating that the lithium-ion battery of this application has good cycle performance and safety performance.
[0141] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
[0142] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method or article.
[0143] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
Claims
1. A positive electrode plate, comprising a positive electrode current collector, a first coating and a positive electrode material layer, wherein the first coating is disposed on the surface of the positive electrode current collector, and the positive electrode material layer is disposed on the surface of the first coating away from the positive electrode current collector, the first coating comprises a lithium-containing material and a conductive material, the Dv99 of the lithium-containing material is 500nm to 1000nm, and the specific surface area of the lithium-containing material is 5m 2 / g to 50m 2 / g.
2. The positive electrode sheet according to claim 1, wherein: The Dv99 of the lithium-containing material is 500nm to 700nm.
3. The positive electrode sheet according to claim 1, wherein: The specific surface area of the lithium-containing material is 30 m 2 / g to 50m 2 / g.
4. The positive electrode sheet according to claim 1, wherein: The lithium-containing material satisfies at least one of the following conditions: (1) The Dv50 of the lithium-containing material is 50 nm to 200 nm; (2) The powder resistivity of the lithium-containing material is 50 Ω·cm to 100 Ω·cm.
5. The positive electrode sheet according to claim 1, wherein: The lithium-containing material includes at least one of lithium iron phosphate, lithium cobalt oxide, lithium iron manganese phosphate or lithium silicate; based on the mass of the first coating, the mass percentage of the lithium-containing material is 50% to 70%.
6. The positive electrode sheet according to claim 1, wherein: The conductive material includes at least one of SnO2, In2O3, CoO, TiO2 or Cr2O3; based on the mass of the first coating, the mass percentage of the conductive material is 20% to 45%.
7. The positive electrode sheet according to claim 6, wherein: The conductive material further includes a doping element, and the doping element includes at least one of Sb, F or B; based on the mass of the conductive material, the mass percentage of the doping element is 0.5% to 5%.
8. The positive electrode sheet according to claim 7, wherein: Based on the mass of the conductive material, the mass percentage of the doping element is 0.5% to 2%.
9. The positive electrode sheet according to claim 1, wherein: The conductive material satisfies at least one of the following conditions: (1) The Dv50 of the conductive material is 50nm to 200nm; (2) The powder resistivity of the conductive material is 5 Ω·cm to 20 Ω·cm.
10. The positive electrode sheet according to claim 1, wherein: The first coating layer also includes a first binder, which includes a water-soluble metal salt compound; based on the mass of the first coating layer, the mass percentage of the first binder is 5% to 10%.
11. The positive electrode sheet according to claim 10, wherein: The water-soluble metal salt compound includes alkali metal polyacrylate and / or alkaline earth metal polyacrylate, the alkali metal polyacrylate includes at least one of sodium polyacrylate, lithium polyacrylate or potassium polyacrylate, and the alkaline earth metal polyacrylate includes at least one of calcium polyacrylate or magnesium polyacrylate.
12. The positive electrode sheet according to claim 1, wherein: The thickness of the first coating layer is 0.5 μm to 2 μm, and the porosity of the first coating layer is 10% to 20%.
13. The positive electrode sheet according to claim 12, wherein: The thickness of the first coating layer is 0.5 μm to 1 μm.
14. The positive electrode sheet according to claim 1, wherein: The bonding force between the first coating layer and the positive electrode current collector is 500 N / m to 2000 N / m.
15. The positive electrode sheet according to claim 14, wherein: The bonding force between the first coating layer and the positive electrode current collector is 500 N / m to 1000 N / m. 16 . An electrochemical device, comprising the positive electrode sheet according to claim 1 .
17. An electronic device comprising the electrochemical device according to claim 16.